Komunikasi Keluarga Dan Media Baru (Studi Kasus Pergeseran Pola Komunikasi Keluarga pada Masyarakat Urban di Jakarta) - Riyodina G Pratikto (Sekolah Tinggi Ilmu Komunikasi Inter Studi, 2017)
The presence of new media (the new media) through the internet, manifesting human wishes and hopes to be able to communicate with a broad reach, without having to be limited again space and time. The development of technology in the field of communication, not only bring new media, but further makes the shift in the pattern of communication in other aspects of human life, such as a change in the process of communication or interaction. Shifting patterns of communication in this community also by itself make the pattern of communication that occurs in a group, the family also experienced a shift. The purpose of this study, is to determine the existence of a shift in interpersonal communication patterns that occur in a family, with the presence of new media. Thus can be known steps - steps of anticipation due to shifting patterns of interpersonal communication within the clan. The theory used Osgood and Schramm communication model. The research method is case study. Data collection with in-depth interviews and observation. The results of this study can further illustrate the shifting of communication patterns from family communication to family mediated communication. The shift in communication patterns caused by new media is positive and negative. The anticipation of the shift in communication patterns in this family, using more face-to-face and two-way communication.